Joy Of Gıg Work?! A Study Of Malaysıan Gıg Workers - Sean Kwanx Jun Jie; Low Mei Peng (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2023)
The gig economy is taking up a substantial portion of the workforce in recent years, be it globally or in Malaysia. The nature of gig work brought out the concern for gig workers’ well-being whereby most of the gig work is interrupting their daily routine. Thus, the level of gig workers’ happiness call for attention. The gig workers’ happiness should receive equal attention as the conventional workers. With this set the significance to study the joy of gig work. Also, at present, there is a knowledge gap of gig workers. This study aims to identify the determinant of the joy of gig work. Generally, the Joy of Gig Work is the intense pleasure or happiness brought on by something very satisfying or wonderful in a gig working environment. This study focused on low-skilled gig workers in Malaysia through judgmental sampling technique. A total of 212 survey responses were collected for analysis. The findings indicated that job autonomy has no significant relationship with the joy of gig work, while motivation and work-life balance does bring effect on joy of gig work. The findings of this study contribute to society especially to the economy, company platform and individuals that consider participating in gig economy.